Penyuluhan Cara Mengenali Tanda Dan Gejala Penyakit Menular Seksual Serta Pencegahannya Kepada Para Pelajar Di SMAN1 Silima Pungga Pungga - Saharnauli Janna Verawaty Simorangkir (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
During adolescence, a person tends to be more motivated to explore sexual experiences and if done without guidance and direction, it can cause adolescents to engage in risky sexual behavior. One of the risks of active sexual behavior is Sexually Transmitted Diseases (STDs). The purpose of this activity is to provide knowledge about how to recognize the signs and symptoms of PMS and STD prevention efforts to students at SMAN 1 Silima Pungga Pungga. The method of this activity is question and answer counseling and games. This activity was considered quite successful, judged by the enthusiasm of the participants to ask questions and feedback from participants who stated that this counseling was considered interesting and useful.